CCNA wireless study guide - Lammle, Todd; Cisco Networking Academy Program (Indianapolis, Ind Wiley Technology Pub, 2010)
"A complete guide to the CCNA Wireless exam by leading networking authority Todd Lammle. The CCNA Wireless certification is the most respected entry-level certification in this rapidly growing field. Todd Lammle is the undisputed authority on networking, and this book focuses exclusively on the skills covered in this Cisco certification exam. The CCNA Wireless Study Guide joins the popular Sybex study guide family and helps network administrators advance their careers with a highly desirable certification. The CCNA Wireless certification is the most respected entry-level wireless certification for system administrators looking to advance their careers. Written by Todd Lammle, the leading networking guru and author of numerous bestselling certification guides. Provides in-depth coverage of every exam objective and the technology developed by Cisco for wireless networking. Covers WLAN fundamentals, installing a basic Cisco wireless LAN and wireless clients, and implementing WLAN security. Explains the operation of basic WCS, basic WLAN maintenance, and troubleshooting. Companion CD includes the Sybex Test Engine, flashcards, and entire book in PDF format. Includes hands-on labs, end-of-chapter review questions, Exam Essentials overview, Real World Scenarios, and a tear-out objective map showing where each exam objective is covered. The CCNA Wireless Study Guide prepares any network administrator for exam success."--Provided by publisher
Wireless networks and topologies -- WLAN RF fundamentals -- Spread spectrum technologies and modulations -- Wireless regulation bodies, standards, and certifications -- Introduction to wireless security
"Covers all exam objectives for IUWNE Exam 640-721."
Includes index
1
Keywords: Telecommunications engineers -- Certification -- Study guides; Wireless LANs -- Examinations -- Study guides